Traditional Arctic native fish storage methods and their role in the sustainable development of the Arctic - Ying, Luo; Lobanov, Andrew Alexandrovich; Fengming, Hui; Andronov, Sergei Vasilevich; Lobanova, Lidiya Petrovna; Bogdanova, Elena Nikolaevna; Grishechkina, Irina Alexandrovna; Popov, Andrei Ivanovich; Fedorov, Roman Yurievich (Polar Research Institute of China - PRIC, 2021)
The business of the Arctic has received increased attention owing to climate change. However, resource development and the use of waterways threaten the fragile Arctic ecology. The indigenous people of the Arctic have acquired a vast amount of traditional knowledge about coexisting in harmony with nature over the course of many years. Herein, five types of fish storage facilities that are commonly used by Arctic indigenous people and their working mechanisms are described. The traditional knowledge of the Arctic indigenous people is practically applied in Arctic fish storage systems, which are still common, effective, and environmentally friendly. The traditional fish storage facilities of the aborigines are of significance because they promote the sustainable development of the Arctic.